Synthesis and Reactivity of Novel Boranes Derived from Bulky Salicylaldimines: The Molecular Structure of a Maltolato Compound - Jeremy L. Bourque; Stephen J. Geier; Christopher M. Vogels; Andreas Decken; Stephen A. Westcott (Crystals, 2015)
Reductive amination of salicylaldehyde or 3,5-di-tert-butylsalicylaldehyde and 1-adamantylamine using NaBH4 gave the corresponding aminoalcohols in high yields. Subsequent addition of one equivalent of H3B·SMe2 to the aminoalcohols, with loss of two equivalents of dihydrogen, resulted in the formation of adamantanyl oxazaborinanes (1a,b). The molecular structure of 1b was studied by a single crystal X-ray diffraction study. Crystals were obtained from a saturated Et2O solution and belong to the triclinic space group Pī with unit cell parameters a = 9.1267(4) Å; b = 11.676(2) Å; c = 12.240(3) Å; α = 66.840(3)°; β = 78.529(3)°; and γ = 67.354(3)°. The molecular structure of the addition product (2a) arising from maltol and 1a was also confirmed by single crystal X-ray diffraction. Crystals were obtained from a saturated 1:2 mixture of toluene/Et2O and belong to the orthorhombic space group Pna2(1) with unit cell parameters a = 18.519(6) Å; b = 17.315(5) Å; and c = 12.680(4) Å. The asymmetric unit contains two molecules that differ slightly in some of the dihedral angles.